"I am dependent on others to get there": Mobility barriers and solutions for societal participation by persons with disabilities. (January 2023) - Neven, An; Ectors, Wim
Highlights: Different target groups of persons with disabilities (PWD) were included. Various problems of the complete travel chain cause PWD to be dependent on others. Significant transport barriers of PWD were related to both environmental and personal factors. Specific recommendations are drawn up to optimize the travel behaviour of PWD with societal participation enhancement in daily life. Abstract: Transportation challenges are important barriers for persons with disabilities (PWD) to participate in professional, social and economic life. This study builds further on previous literature about the transportation problems of PWD by not only mapping in detail the perceived mobility barriers of PWD with various types of disabilities and for different travel modes, but also investigating their own solutions to lower these barriers and examining the impact of improved mobility on participation. The experiences, transport needs and wishes of 45 PWD (with physical, visual or intellectual disabilities or Autism Spectrum Disorder) were investigated using qualitative focus groups and semi-structured interviews in Flanders, Belgium. The study provides concrete recommendations for the experienced mobility barriers to increasing PWD's societal participation.